2016
DOI: 10.1038/cddis.2016.32
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK regulates the Wnt inhibitor Dickkopf-1 in osteotropic prostate cancer cells

Abstract: The Wnt inhibitor Dickkopf-1 (DKK-1) has been associated with the occurrence of bone metastases in osteotropic prostate cancer by inhibiting osteoblastogenesis. P38 mitogen-activated protein kinase (MAPK) activity is also dysregulated in advanced prostate cancer. However, the impact of p38 MAPK signaling on DKK-1 remains unknown. Inhibition of p38 MAPK signaling in osteolytic PC3 cells by small molecule inhibitors (doramapimod, LY2228820 and SB202190) suppressed DKK-1 expression, whereas activation of p38 MAPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 52 publications
3
31
0
1
Order By: Relevance
“…Several studies have identified p38g inhibitors as promising therapeutic agents for many tumor types; such as colon (Yin et al, 2015), prostate (Browne et al, 2016), esophageal (Zheng et al, 2016), and breast cancers (Qi et al, 2015). In addition to activity against CTCL, the p38g inhibitor we identified, F7/PIK75, also shows activity against cells derived from several types of cancers, including prostate, ovarian, and breast cancers (see Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have identified p38g inhibitors as promising therapeutic agents for many tumor types; such as colon (Yin et al, 2015), prostate (Browne et al, 2016), esophageal (Zheng et al, 2016), and breast cancers (Qi et al, 2015). In addition to activity against CTCL, the p38g inhibitor we identified, F7/PIK75, also shows activity against cells derived from several types of cancers, including prostate, ovarian, and breast cancers (see Supplementary Table S2).…”
Section: Discussionmentioning
confidence: 89%
“…4 A and 4 B). In addition, anisomycin, a chemical activator of p38 [34] , partially reversed the effects of chloroquine on oxalate-induced p38 phosphorylation, cell viability inhibition, LDH release, ROS generation and membrane potential losses, whereas had no significant effect on chloroquine-mediated ratio of LC3 II/LC3 I ( Figs. 4 C- 4 G).…”
Section: Resultsmentioning
confidence: 99%
“…Mammals express at least four distinctly regulated groups of MAPKs including extracellular signal‐related kinases (ERK)‐1/2, Jun amino‐terminal kinases (JNK1/2/3), p38MAPK proteins (p38MAPK has α/β/γ/δ isoforms) and ERK5 which are activated by specific upstream MAPK Kinases (MAPKKs, or MEKs). MAPK signalling activates at least 20 transcription factors, and is involved in a series of other signalling pathways …”
Section: Molecular Mechanismsmentioning
confidence: 99%